Economic Costs of the Karabakh Conflict: 1992 - 2023 - Daubenmire, John (ADA University, 2024)
The true costs of engaging in war are far greater than just financial. Studies on the cost of war have been conducted for various global conflicts, but no summative economic costing exists from the Azerbaijani perspective for the totality of the Karabakh Conflict with Armenia between 1992-2023. This paper examines some of the methodological challenges of wartime accounting and applies costing strategies to determine not only the direct expenses of engaging in this particular armed conflict, but also the losses, indirect costs, and impacts on economic development. An evaluation of budgeted expenses and excess expenditure through defense spending, reconstruction, demining, and refugee and IDP support is included for the country of Azerbaijan. Economic costs and losses of economic potential are presented in terms of impact to investment, human capital, productivity, capital assets, natural resources, and international relations, with a special analysis to determine opportunity cost. Utilizing conservative assumptions, the financial expenditure necessary for Azerbaijan to restore its territorial integrity in the Karabakh region far exceeds $50 billion dollars with a much higher cost to future generations and the economic potential of the country as a whole.
Keywords: Azerbaijan -- Economic conditions -- 1991-2023; War -- Economic aspects -- Azerbaijan; Azerbaijan -- Politics and government; Nagorno-Karabakh Region -- History -- 1991-2023; Public and International Affairs